Osteogenic Cell Cultures Cannot Utilize Exogenous Sources of Synthetic Polyphosphate for Mineralization. Issue 12 (15th October 2014) - Ariganello, Marianne B.; Omelon, Sidney; Variola, Fabio; Wazen, Rima M.; Moffatt, Pierre; Nanci, Antonio
ABSTRACT Phosphate is critical for mineralization and deficiencies in the regulation of free phosphate lead to disease. Inorganic polyphosphates (polyPs) may represent a physiological source of phosphate because they can be hydrolyzed by biological phosphatases. To investigate whether exogenous polyP could be utilized for mineral formation, mineralization was evaluated in two osteogenic cell lines, Saos‐2 and MC3T3, expressing different levels of tissue non‐specific alkaline phosphatase (tnALP). The role of tnALP was further explored by lentiviral‐mediated overexpression in MC3T3 cells. When cells were cultured in the presence of three different phosphate sources, there was a strong mineralization response with β‐glycerophosphate (βGP) and orthophosphate (Pi) but none of the cultures sustained mineralization in the presence of polyP (neither chain length 17‐Pi nor 42‐Pi). Even in the presence of mineralizing levels of phosphate, low concentrations of polyP (50 μM) were sufficient to inhibit mineral formation. Energy‐dispersive X‐ray spectroscopy confirmed the presence of apatite‐like mineral deposits in MC3T3 cultures supplemented with βGP, but not in those with polyP. While von Kossa staining was consistent with the presence or absence of mineral, an unusual Alizarin staining was obtained in polyP‐treated MC3T3 cultures. This staining pattern combined with low Ca:P ratios suggests the persistence of Ca‐polyP complexes, even with high residual ALP activity. In conclusion, under standard culture conditions, exogenous polyP does not promote mineral deposition. This is not due to a lack of active ALP, and unless conditions that favor significant processing of polyP are achieved, its mineral inhibitory capacity predominates. J. Cell. Biochem. 115: 2089–2102, 2014. © 2014 Wiley Periodicals, Inc.